2008
DOI: 10.1111/j.1440-1746.2008.05326.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed gastrointestinal motility and decreased interstitial cells of Cajal in diabetic db/db mice

Abstract: We demonstrated disturbed gastrointestinal motility in db/db mice with reduced areas of ICC and expression of SCF. Our results suggest the involvement of ICC in the gastroenteropathy of type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 32 publications
(47 reference statements)
5
57
0
Order By: Relevance
“…The purpose of that study was to correlate the expected decrease in slow wave propagation with the reported decrease in the census of ICC-MY in the small intestine (8,10,20,30). To our initial surprise, we did not measure a significant decrease in slow wave propagation although there was a reduction in the number of ICC-MY by ϳ50% (10).…”
mentioning
confidence: 86%
“…The purpose of that study was to correlate the expected decrease in slow wave propagation with the reported decrease in the census of ICC-MY in the small intestine (8,10,20,30). To our initial surprise, we did not measure a significant decrease in slow wave propagation although there was a reduction in the number of ICC-MY by ϳ50% (10).…”
mentioning
confidence: 86%
“…7,11 Kit mRNA and KIT protein levels decline in the colons of patients with slow-transit constipation. 12,13 In addition, stem cell factors and KIT protein activity is closely related to the development and sustenance of ICCs, and their expression levels decrease with age in the rat ascending colon (AC). [14][15][16] Neuronal degeneration in the enteric nervous system is an important mechanism of age-related functional changes in the guts of older animals.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ICC express protooncogene c-kit (6,47). The stem cell factor (SCF) is a natural ligand of Kit (50) and involves the development and maintenance of ICC (35). It has been known that the expression of c-kit mRNA and c-Kit protein significantly decreased in the colon of patients with slow-transit constipation and mice with diabetes mellitus (44,50).…”
mentioning
confidence: 99%
“…The stem cell factor (SCF) is a natural ligand of Kit (50) and involves the development and maintenance of ICC (35). It has been known that the expression of c-kit mRNA and c-Kit protein significantly decreased in the colon of patients with slow-transit constipation and mice with diabetes mellitus (44,50). In addition, there was a study on the number and volume of ICC networks in the normal human stomach and colon, which declined with aging (15).…”
mentioning
confidence: 99%